The stonecutter eaudiobook - Läckberg, Camilla (Fjällbacka, 2012)
The remote resort town of Fjallbacka has seen more than its share of tragedies, but a little girl found in a fisherman's net may be the worst yet-especially when the postmortem reveals that this was a methodical murder, not an accidental drowning. Local detective Patrik Hedstrom has just become a father, and it's his grim task to discover who could have killed a child both he and his partner Erica knew well. He realizes that the solution lies with finding a motive for this terrible crime. Although Hedstrom is no stranger to the criminal mind, he couldn't possibly predict how this case will reach into Fjallbacka's darkest heart, spanning generations and ripping aside its idyllic facade, perhaps forever.